The THE INFLUENCE OF CONTINUITY OF CARE (COC) TO THE INCREASING OF COGNITIVE, AFFECTIVE AND PSYCHOMOTOR ASPECTS OF MIDWIFERY CARE TO STUDENTS OF MIDWIFERY STUDY PROGRAM - Lasiyati Yuswo Yani; Ariu Dewi Yanti (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2019)
Education should be able to form graduate competencies in accordance with community needs. The quality of midwives in Indonesia is still low, this is indicated by the passing of the competency test which tends to be volatile (RistekDikti, 2016). During this time the learning aspects are given fragmented and separate. Learning models are needed in accordance with the needs of the community, integrating all aspects related to community values and are dynamic according to the needs of the community. The purpose of this study was to find the effect of CoC learning methods on improving cognitive, affective and psychomotor midwifery students. This study used "quasi-experimental non-equivalent pre-post test randomized intervention studies". Each student was assessed on affective, cognitive, and psychomotor aspects in the implementation of midwifery care in the 5th semester before and after the implementation of CoC, Each midwifery student carries out CoC care for a participant. The results of the multivariate analysis using the Wilks' Lambda test showed that the greatest effect of time effect on affective variables was shown by the results of Partial Eta Squared 0.982, meaning that time could explain 98.2% of the variance in the multivariate value. It means that this learning method is proven to improve student learning experiences. Keywords: Clinical Learning, CoC, Cognitive, Affective, Psychomoto